How do different surgical techniques for haemorrhoidectomy (e.g., stapled vs. excisional) compare in terms of postoperative complications and patient recovery? : A Systematic Review - Septian Tri Anggara; Andy Michael; Tia Rahmi Priyanto (International Medical Journal Corp. Ltd, 2025)
Introduction: Conventional excisional hemorrhoidectomy, while effective for high-grade hemorrhoids, is frequently associated with significant postoperative pain and a prolonged recovery period. Newer modalities, such as stapled hemorrhoidopexy and energy-based devices, have been developed to minimize trauma and improve patient outcomes. This systematic review provides a comprehensive comparative analysis of these surgical techniques, focusing on postoperative complications and patient recovery metrics. Methods: Following the PRISMA 2020 guidelines, a systematic search was conducted across PubMed, Semantic Scholar, Springer, and Google Scholar to identify relevant studies. The review included randomized controlled trials (RCTs) that compared at least two surgical techniques for hemorrhoidectomy in adult patients and reported on outcomes such as pain, recovery time, or complications. A total of 11 RCTs met the eligibility criteria for the final analysis. Results: The analysis revealed that modern techniques—specifically energy-based devices (e.g., Ligasure, harmonic scalpel) and stapled hemorrhoidopexy—consistently resulted in significantly lower postoperative pain scores compared to traditional excisional methods. These benefits were accompanied by reduced needs for analgesia, shorter hospital stays, and a faster return to normal activities. Furthermore, energy devices were associated with shorter operative times and a significantly lower incidence of specific complications, such as postoperative bleeding. Conclusion: Modern surgical techniques offer a substantially improved postoperative experience for patients undergoing hemorrhoidectomy. The reduction in pain, faster recovery, and lower rates of specific complications support the adoption of energy-based and stapled techniques as a new standard of care. While overall safety profiles are comparable to traditional methods, these advanced procedures provide clear, clinically meaningful benefits. Further research with long-term follow-up is recommended to assess recurrence rates and cost-effectiveness.